Platform Work and Economic Insecurity: Evidence from Italian Survey Data - Valeria Cirillo; Dario Guarascio; Zachary Parolin (Global Labor Organization (GLO), 2021)
The emergence of the platform economy has served as a defining feature of increasing fragmented labour markets in modern economies. Recent research on platform work, however, has struggled to quantify the socio-economic conditions of platform workers relative to other occupation groups. Moreover, it remains unclear if the socio-economic disadvantages that platform workers are likely to face are primarily channeled through lower incomes or their more precarious working conditions. This study uses representative survey data of platform workers in Italy to investigate their size, composition, and socio- economic conditions relative to individuals in other occupations. Our findings reveal that platform workers tend to be students and of younger age, but are diverse with respect to sex, educational attainment, and native-born status. We find that platform workers face greater economic insecurity relative to all other occupation classes. Strikingly, they also feature a rate of economic insecurity that is not significantly different from that of unemployed adults. Moreover, we find that the higher levels of insecurity are not primarily channeled through lower incomes; instead, higher rates of insecurity persist even when taking family incomes into account, suggesting that the precarity and volatility of platform work matter as much as income differences in shaping economic disadvantage. Results hold under analyses that account for selection into platform work. Our findings carry important consequences for understandings of the intensity and sources of socio- economic disadvantage of individuals engaged in platform work.
Keywords: J40; J80; J81; 330; platform work; non-standard work; economic insecurity